2018
DOI: 10.1108/qmr-06-2016-0050
|View full text |Cite
|
Sign up to set email alerts
|

Brand addiction conceptual development

Abstract: Purpose Although emerging literature has discussed different consumer–brand relationships and addictive behavior constructs, to date, it has not explored the brand addiction phenomenon. This study aims to undertake a conceptual inspection to better understand the nature of the brand addiction phenomenon, thereby providing a clear and concise conceptual definition. Design/methodology/approach To develop a concise definition of brand addiction, the researcher applies a conceptual development procedure, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 51 publications
1
53
0
1
Order By: Relevance
“…Romantic love, however, showed dispositions toward more impulsive, intimate, and passionate relationships compared to brand love. The marketing literature stresses the importance of building impulsive, intimate, and passionate relationships between brands and consumers (Shimp and Madden, 1988;Fournier, 1998Fournier, , 2014Keller, 2001;Thomson et al, 2005;Carroll and Ahuvia, 2006;Park et al, 2008;Albert et al, 2009;Albert and Valette-Florence, 2010;Lastovicka and Sirianni, 2011;Sarkar, 2011;Batra et al, 2012;Sarkar et al, 2012;Cui et al, 2018;Mrad, 2018). Thus, while these strong emotions are important elements for brand love, we did not observe activation of brain regions related to impulsive, intimate, and passionate relationships in brand love in the present study.…”
Section: Different Brain-activated Regions: Brand Love and Typical Inmentioning
confidence: 99%
“…Romantic love, however, showed dispositions toward more impulsive, intimate, and passionate relationships compared to brand love. The marketing literature stresses the importance of building impulsive, intimate, and passionate relationships between brands and consumers (Shimp and Madden, 1988;Fournier, 1998Fournier, , 2014Keller, 2001;Thomson et al, 2005;Carroll and Ahuvia, 2006;Park et al, 2008;Albert et al, 2009;Albert and Valette-Florence, 2010;Lastovicka and Sirianni, 2011;Sarkar, 2011;Batra et al, 2012;Sarkar et al, 2012;Cui et al, 2018;Mrad, 2018). Thus, while these strong emotions are important elements for brand love, we did not observe activation of brain regions related to impulsive, intimate, and passionate relationships in brand love in the present study.…”
Section: Different Brain-activated Regions: Brand Love and Typical Inmentioning
confidence: 99%
“…With respect to environment-related determinants, respondents were influenced mainly by the branding factor, with a high average of 3.4308, followed by taste of relaxation, market trends, and social drinker. Going by the fact that brand addiction is a psychological state that entails an emotional attachment to a particular brand, driven by compulsive urges that generally provide ‹ 44 › pleasure (Mrad, 2018), it is inferred that the elderly usually pay more attention to the brand than market trends and social drinking.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Against this background, the current study aims to empirically analyze further brand addiction consequences identified by previous contributions (Mrad, 2018;Cui et al, 2018), which have not yet been tested by the existing literature (i.e. irritability, compulsive buying behaviors toward the brand and brand exclusiveness).…”
Section: Addictive Brand Outcomesmentioning
confidence: 99%
“…Brand addiction represents one of the most intense brandconsumer relationships (Cui et al, 2018). However, even if currently some studies Cui et al, 2018;Mrad, 2018;Mrad and Cui, 2017) focused their attention on this construct, brand addiction within the literature is a very recent phenomenon and research studies remain rare . Despite this scarcity of studies, some authors have still sought to conceptualize brand addiction systematically.…”
Section: Brand Addiction Conceptualizationmentioning
confidence: 99%
See 1 more Smart Citation